Prevalence and Antimicrobial Susceptibility of Escherichia Coli O157 Isolated From Raw Milk Marketed in Chittagong, Bangladesh - Md. Kauser-Ul Alam; Shireen Akther; Nazmul Sarwar; Shamsul Morshed; Goutam Kumar Debnath (Turkish Journal of Agriculture: Food Science and Technology, 2017)
Escherichia coli is an emerging public health concern in most countries of the world. It is an important cause of food-borne human disease. The present study assessed the prevalence and determined the antibiotic resistance patterns of E. coli from raw milk marketed in Chittagong, Bangladesh. Of the raw milk marketed in Chittagong ~33(18%) of the 186 raw milk samples of it contains E. coli, indicator bacteria for any enteric pathogens. The mean viable count of total bacteria was 4.04×108 cfu/ml and the mean viable count of E. coli in the contaminated raw milk was 1.88×106 cfu/ml. E. coli from only six (18.2%) of the 33 positive samples yielded colourless colonies across the CT-SMAC, suggesting the probable presence of populations belonging to the serotype O157 and rest of the isolates 27 (81.82%) produced coloured colony on CT-SMAC considering the probable presence of populations belonging to the serotype non-O157. Growth of probable E. coli O157, as evidenced by the colourless colonies on CT-SMAC compared to coloured colonies from other bacteria. Confirmed isolates were further subjected to antimicrobial susceptibility test using the Agar disc diffusion technique. Antibiotics susceptibility profile showed that all the isolates in case of E. coli O157, penicillin (100%), tetracycline (100%), amoxicillin (83.33%) and erythromycin (83.33%) were the most resistant whereas ciprofloxacin (66.67%), gentamicin (50.0%), and streptomycin (50.0%) were the most sensitive antibiotics. In case of E.coli non-O157 susceptibility profile showed that chloramphenicol (40.74%), erythromycin (40.74%) and oxacillin (37.04%) were the most resistant whereas ciprofloxacin (70.37%), sulphamethoxazole/trimethoprim (S/T) (59.26%) and gentamycin (55.55%) were the most sensitive antibiotics. The antimicrobial resistance exhibited by E. coli O157and non-O157 strains in this study is an indication of possible antibiotic abuse.